Immunogenicity of Two Fractional Inactivated Poliovirus Vaccine Doses vs Single Intramuscular Inactivated Poliovirus Vaccine Dose in Infants of Low- and Middle-income Countries: A Prospective Case-control Study - Kunal Kumar; Sangita Yadav; Raghvendra Singh; Archana Thakur (Pediatric Infectious Disease)
Aims and background: Despite the support of the Global Alliance for Vaccines and Immunization, developing countries still struggle to afford inactivated polio vaccine (IPV). This study was undertaken to evaluate and compare the serological status of infants being offered two doses of intradermal fractional inactivated polio vaccine (ID-f-IPV) vs a single full dose administered intramuscularly (IM-SD-IPV) in conjunction with routine bivalent oral poliovirus vaccine (bOPV). Materials and methods: This prospective cross-sectional study was conducted in an Indian tertiary care healthcare center. The study consisted of 80 participants, with 40 in each group. The study measured the levels of antibodies using human poliovirus (PV) antibody immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) kits and identified seroprotection as the presence of antibody >1:8 dilution. Seroconversion was described as a fourfold rise in antibody titers after 4 weeks. Results: Pre- and postimmunization mean antibody titers (MAT) in pg/mL against types I, II, and III PVs in the ID group were 192.26 ± 49.5, 162.96 ± 34.1, 131.32 ± 38.4, and 1743.58 ± 391.6, 1272.10 ± 341.3, 1105.71 ± 331.1, respectively. However, in the IM group, they were 523.83 ± 102.5, 209.47 ± 57.3, 426.57 ± 61.7, 2101.32 ± 282.1, 1033.08 ± 226.1, and 1381.04 ± 308.3, respectively. Around 100% of participants in both groups were seroprotected at pre- and postimmunization levels. Seroconversion against types I, II, and III serotypes in the ID-f-IPV group was 100% each, while in the IM-SD-IPV group, it was 62.5, 87.5, and 55%, respectively. Conclusion: The seroconversion rates of f-IPV were superior to the full dose IPV and may be a cost-effective choice for low- and middle-income countries.